1988
DOI: 10.1177/088391158800300106
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Vinyl Polymer by Fixing 5-Fluorouracils through Organosilicon Groups via Carbamoyl Bonds and Its Antitumor Activity

Abstract: Some vinyl polymers by fixing 5FUs via carbamoyl bonds on organosilicon groups were synthesized by means of ordinary radical polymerization of the corresponding monomers. These hybrid type vinyl polymers with 5FU and or ganosilicon amine units exhibited significant antitumor activities against p-388 lymphocytic leukemia in mice in vivo (i.p./i.p.). The effects of the molecu lar weight, the hydrophobicity of the polymer carrier, the number of methy lenes in the spacer group, and the presence of silicon on the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1989
1989
1993
1993

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Ouchi 15 reported that carbamoyl bonds in the conjugates of 5FU and vinyl polymeric carriers could be perfectly hydrolyzed by refluxing in 5 N NaOH aq. soln.…”
Section: Preparation and Determination Of The Composition Of The Conjmentioning
confidence: 99%
“…Ouchi 15 reported that carbamoyl bonds in the conjugates of 5FU and vinyl polymeric carriers could be perfectly hydrolyzed by refluxing in 5 N NaOH aq. soln.…”
Section: Preparation and Determination Of The Composition Of The Conjmentioning
confidence: 99%